Penerapan Pembelajaran Matematika Realistik untuk Meningkatkan Kemampuan Pemecahan Masalah Matematik Siswa Di MIN 2 Padangsidimpuan - Sari, Lili Nur Indah (IAIN PADANGSIDIMPUAN, 2020)
This study aims to improve the ability to solve mathematical problems with the application of realistic mathematics learning. From the students' initial abilities, it can be seen that students in class V MIN 2 Padang sidimpuan still have a fairly low average grade. The study used classroom action research as much as 2 cycles. The subjects of this study were students of class V MIN 2 Padangsidimpuan which were primary data. The research instrument in this study was a test of students' mathematical problem solving abilities and observation sheets. Based on the results of data analysis, it can be concluded that the average increase in students' mathematical problem solving ability from the initial test is 19.833 (19.833%) categorized as very poor to 51.083 (51.083%) which is not good enough in the first cycle and becomes 83.083 (83.083%) in the good category in the cycle II.